2011
DOI: 10.1094/ats-2011-0325-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Fall Applications of Mesotrione For Annual Bluegrass Control in Kentucky Bluegrass

Abstract: Annual bluegrass (Poa annua L.) is a problematic weed on golf courses, sports turf, sod production fields, and irrigated lawns, but few options exist for control of annual bluegrass in Kentucky bluegrass (Poa pratensis L.). However, mesotrione has shown promising activity against annual bluegrass and adequate turf safety on Kentucky bluegrass. Experiments were completed from 2004 through 2010 in Urbana, IL, and/or West Lafayette, IN, to refine application strategies for annual bluegrass control with mesotrione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 20 publications
4
30
0
Order By: Relevance
“…Kentucky bluegrass has superior tolerance to mesotrione compared to annual bluegrass, and treatments did not inhibit tillering from the nontreated at any growth stage. These results support previous observations on the differential tolerance levels of annual bluegrass to mesotrione at various stages of maturity in field experiments (Reicher et al 2011;Skelton et al 2012). POST applications of mesotrione at 140 and 210 g ha À1 applied 4 wk after emergence did not reduce Kentucky bluegrass cover from the nontreated (Venner 2011).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Kentucky bluegrass has superior tolerance to mesotrione compared to annual bluegrass, and treatments did not inhibit tillering from the nontreated at any growth stage. These results support previous observations on the differential tolerance levels of annual bluegrass to mesotrione at various stages of maturity in field experiments (Reicher et al 2011;Skelton et al 2012). POST applications of mesotrione at 140 and 210 g ha À1 applied 4 wk after emergence did not reduce Kentucky bluegrass cover from the nontreated (Venner 2011).…”
Section: Resultssupporting
confidence: 92%
“…Multiple applications of mesotrione in the fall provided inconsistent levels of annual bluegrass control across locations and years (Reicher et al 2011). Skelton et al (2012) also reported erratic control following mesotrione at 110 or 186 g ha À1 applied POST five and three times in Kentucky bluegrass, respectively.…”
mentioning
confidence: 99%
“…Though mesotrione is not specifically labeled for postemergence control of ABG, it is labeled for preemergence suppression of ABG and for use on KBG fairways (Anonymous, 2011). Work in Indiana and Illinois indicates that optimum ABG control in the fall results from three applications of mesotrione at 3.0 or 5.0 oz/ac/application at 14‐day intervals, starting in mid‐ to late September (Reicher et al, 2011). Three fall applications of ethofumesate has been the standard for controlling ABG in KBG and/or PRYE fairways (Adams, 1989; Lewis and DiPaola, 1989; Johnson et al, 1989; Shearman, 1986; Dernoeden and Turner 1988).…”
Section: Useful Conversionsmentioning
confidence: 99%
“…Under highly maintained turf settings, ABG converts to a perennial life cycle over time requiring the use of a postemergence herbicide application for eradication (Branham et al, 2010). The selective control of ABG in cool-season turf, especially kentucky bluegrass (Poa pratensis L.), can be challenging as a result of limited herbicide options (Reicher et al, 2011).…”
mentioning
confidence: 99%